ANALISIS KUALITAS PENERIMAAN SINYAL USB WIFI EKSTERNAL BERDASARKAN KETINGGIAN DAN JARAK AKSES POINT - sasa ani arnomo (Universitas Putera Batam, 2015)
Wi-Fi is a technology that is growing at the moment, because of the advantages and ease of supporting mobility for work, communication and many other things. To connect to the wireless network, then any device no longer need an additional device to help connect to the network. The device is a wireless adapter. Computers and laptops today the average is equipped with a wireless adapter. Adapter in receiving the signal, there are several levels of strength, the strength of the signal depends on the distance to the signal point of the hotspot or access point. External adapters also can amplify the signal reception of a hotspot. In this study, the research methods were performed using descriptive methods. The data collection technique used observation techniques. By using a data collection was obtained from the assessment of external adapters signal strength, signal strength values ​​detected by the respective software at the same distance, which is 10 yards, scored farther weakened by an external adapter to receive the same hotspot signal.